Perception of e-learning : study on non-CSE major students of BRAC university - Parvez, Md. Sayed Hossan (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.